Sistem Drainase Berwawasan Lingkungan Dengan Konsep Lubang Resapan Biopori Pada Era Pandemi Covid-19 - Nur Anny S. Taufieq; Fhatiah Adiba; Andi Baso Kaswar (Seminar Nasional Pengabdian Kepada Masyarakat, 2020)
This Community Partnership Program (PKM) partner is a teacher at Madrasah Tsanawiyah Pangkep, Pangke Regency. The problem is the environment of the Pangkep Tsanawiyah Madrasah School which has poor environmental drainage and lack of rainwater catchment areas. Therefore, these school teachers need to be equipped with knowledge on how to make water infiltration in a simple way, namely with the concept of Biopore Absorption Holes (LRB). The methods to be used are mentoring methods and participatory rural approach (PRA) methods. The mentoring method is carried out to increase the understanding of school teachers in dealing with environmental drainage, increasing understanding of cleanliness. The PRA method is carried out to generate a sense of belonging to partners for the products to be developed, and a sense of responsibility of partners towards the products and the environment around them. The main methods used in the Community Partnership Program (PKM) activities are lectures, discussions, questions and answers, and simulations. The results achieved are that the LRB can cope with flooding, as a disposal of organic waste, as fertilizer for plants because the organic waste stored in the LRB will turn into compost, and can be used as additional water absorption in the surrounding environment where there are more biopore holes. There are also more water catchment holes in the environment that can help absorb rainwater